2022
DOI: 10.1002/joc.7950
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of non‐tropical cyclone vortices to the rainfall of the Philippines

Abstract: Weaker disturbances than tropical cyclones (TCs) such as tropical depressions and cold surges can significantly induce heavy rainfall and flooding events over the Philippines. However, the analysis of these disturbances including their rainfall contributions are often neglected in previous studies. As the first attempt to address this research gap, this study investigates the rainfall contribution of non‐TC vortices over the Philippines from 1979 to 2020. Only those rainfall‐producing non‐TC vortices that form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
(140 reference statements)
0
0
0
Order By: Relevance
“…Surigao and Hinatuan City stations both have 4% percentage contributions from TC-nonMJO. Such low percentage contributions from TCs alone over Mindanao Island were also noted by Cinco et al (2016), Bagtasa (2017), and Olaguera et al (2023). The contribution from TC-MJO ranges from 0% to 6%, with the largest in Virac station (6%).…”
Section: Contribution Of Tc Lps Cs and Other Disturbances To Extreme ...mentioning
confidence: 73%
See 3 more Smart Citations
“…Surigao and Hinatuan City stations both have 4% percentage contributions from TC-nonMJO. Such low percentage contributions from TCs alone over Mindanao Island were also noted by Cinco et al (2016), Bagtasa (2017), and Olaguera et al (2023). The contribution from TC-MJO ranges from 0% to 6%, with the largest in Virac station (6%).…”
Section: Contribution Of Tc Lps Cs and Other Disturbances To Extreme ...mentioning
confidence: 73%
“…What systems are included in the "other disturbances"? To answer this question, we teased out further the extreme events caused by other disturbances and found that 656 days (16%) out of the 4011 extreme days due to other disturbances matched with the non-TC vortices in Olaguera et al (2023). Hence, the category "other disturbances" used in this study also include disturbances that were not classified as LPS.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We checked whether this vortex has been detected as an LPS, but surprisingly it is not (not shown). Another index for non-TC vortices was used by Olaguera et al (2023) based on Vort and surface winds. We found that this vortex was detected by their index.…”
Section: The Extreme Rainfall Event On January 10 1999mentioning
confidence: 99%